Nefer Jazz Trio & Heikki Rosendahl - Nefer Jazz Trio; Pelo, Riku; Rosendahl, Heikki; Savolainen, Jukka; Uotinen, Riku (Nefer, 2014)
6 kappaletta.
Keywords: Rosendahl, Heikki : albumit; Nefer Jazz Trio : albumit